Avaliação de propostas de produção de textos dissertativo-argumentativos à luz da teoria da argumentação da língua - Hanel, Andréia Inês (2010)
The Argumentative Semantics - especially the Poly phony Theory, proposed by Ducrot(1990), and the Semantic Block s Theory (SBT), presented by Carel in 1992 and developed by both of them, was chosen as a theoretical basis for this research, because we sincerely believe that the principles and linguistic concepts which manage ± they are the ones which best supply the way the argumentations appears in the linguistic relationships used in the speech. From this, the present essay verifies if the argumentative semantics shows theoretical elements which are capable of qualify the comprehension of the essay proposals, the delimitation concerning their themes and also the selection and organization of the arguments during the written production, which can be abbreviated in the following question: the argumentative semantics presents theoretical support which qualify the delimitation of the writing proposals subject ± this delimitation has not just enables the action of justify specific actions as well to transgress ± to argue back according to the SBT, when it establishes that the semantic structures in PT (portaunt ± ³and y et´) are as basics as the structures in DC (donc ± ³therefore´)? The writing proposals were selected as a study object, aiming that the college tests are lik ewise in the follow standard, essential to join this level of education: the applicants need to demonstrate capacity to write a text which contains a level-argumentative context, revealing qualification to use the language and also to be capable of writing their opinions in an effective way, when they have to face a subject. Finally, we wish to contribute, theoretically, for the theme delimitation which are supposed to be in the writings, apart from mak ing possible the citizenship rights, through reflection and enlargement of the critical universe and the diversity of ideas, thank s to the ack nowledgement of the possibility concerning the coexistence of different points of view, a perspective which has already been aspired, by the PCN, as an action which concerns, mainly , to the social change elevation